(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
In the present era skin diseases like atopic dermatitis/eczema get a suitable atmosphere especially in developing countries like India, due to unhygienic living condition, Disturbed life style, Polluted environment and repeated use of chemical additives. This type of diseases make a person feels much more humiliation in society because no one wants to touch them, forbidden by everyone, in that conditions person leads to lack of confidence and feels underestimated mentally as well as physically. Due to this life disturbing condition this disease was chosen for the study. The study was conducted in 30 clinically diagnosed patients of Vicharchika (Atopic Dermatitis) and randomly divided in to two groups, namely group A and group B. Each group has 15 number of patients. Group A is treated with Arka Taila (external application) used twice in a day for 45 days along with Baakuchikadyam Churna for internal consumption (3-6 grams). Group B is treated with Cutis Capsule (2 Capsules) twice a day orally along with external application of Cutis Cream as required for 45 days.